Streamlined project time-cost tradeoff optimization methodology: Algorithm, automation, and application - Nasiri, Sasan; Lu, Ming (Automation in construction, 2022)
The existence of multiple optimum solutions in project Time-Cost Tradeoff (TCT) optimization has not been seriously researched, while the demand on computing time and resources considering project network models of practical size has not been benchmarked. To a certain degree, this has accounted for (1) the lack of commercial software in the market to enable TCT optimization in project management and (2) the absence of applications of TCT optimization in practice. This research proposes a streamlined TCT optimization methodology to generate the first order derivative function of project direct cost against project duration and identify the quantity and position of minimum solution(s) of total project cost. An Excel-based program was prototyped to facilitate validation and computing performance benchmarking using (1) “textbook” examples found in the literature and (2) simulated “test-bed” projects with practical complexity. In conclusion, this research opens the window of opportunity for implementing TCT optimization in practice. •Streamlining project time cost trade-off optimization per first order derivative theory•Analytically determining quantity and position of optimum solutions of project cost•Developing a prototype Excel program to automate the proposed new methodology•Devising a 100-activity project network for benchmarking optimization performances